Fabrication of nanostructured inorganic and carbon porous materials for catalysis and gas storage applications - Masika, Eric (2013)
This thesis details the preparation and subsequent characterisation of novel nanostructured porous materials with tuneable porosity. The main focus is the development of inorganic and carbonaceous porous materials for catalysis, templating and gas storage applications. Three distinct methods of synthesis are investigated, namely: (i) hydrothermal synthesis of zeotype aluminosilicates, (ii) nanocasting techniques for templated carbons and (iii) sol-gel processes, with/without metal salt 'porogen', to carbon aerogels. Post-synthesis modification methods for carbonaceous materials include supercritical carbon dioxide mediated incorporation of palladium nanoparticles into zeolite templated carbons and chemical activation for carbon aerogels resulting in enhanced textural properties. Chapter 1: Provides the foundation and background to the main themes of nanostructured porous materials investigated in this work. Information about fundamental properties and applications is emphasised. Chapter 2: Gives a brief background of techniques used for characterisation of the porous materials generated in this research programme. Gas sorption techniques used to probe hydrogen storage and carbon dioxide uptake are also presented. Chapter 3: Describes stepwise experimental techniques followed in the preparation of various porous materials. The chapter also describes the instrumentation used in these techniques. Chapter 4 - 7: Each chapter reports a separate but sequential area of research in which appropriate additional theory and background is provided with associated literature review. This is followed by a results and discussion section, with a concluding summary for each chapter. Chapter 4: Details the synthesis of ordered mesoporous aluminosilicates, which exhibit some zeolitisation, prepared from a recipe conventionally used for the synthesis of microporous zeolite SEA. The porosity of the aluminosilicates is modified by simple washing and/or refluxing (in water) of either on the as-synthesised mesophase or the calcined material. The aluminosilicates have excellent hydrothermal stability and strong acidity and thus combine the best properties from mesoporous materials and zeolites. Chapter 5: Describes the preparation of zeolite templated carbons (ZTC) generated as replicas of zeolite Y via a hard template nanocasting process. In order to enhance hydrogen storage, the ZTCs are impregnated with Palladium nanoparticles using supercritical carbon dioxide solvent, scC02, as environmentally benign reaction media. The Pd-doped ZTCs exhibit enhanced hydrogen storage due to optimised (with respect to metal content and particle size) incorporation of Pd. Chapter 6: A two-step process for the generation of zeolite template carbons (ZTCs) was investigated. In this case the nanocasting technique involves liquid impregnation of zeolite 13X with furfuryl alcohol followed by chemical vapour deposition (CVD) of ethylene at variable CVD temperatures. The two-step process was a successful attempt to optimise the replication of the zeolite structure in the carbons. The ZTCs had very high surface area and excellent mechanical stability, and achieved the highest hydrogen storage capacity (7.3 wt% at 77 K and 20 bar) ever reported for any carbon material. Chapter 7: Organic Sol-gel chemistry is explored in the formation of carbon aerogels via conventional methods involving the use of resorcinolformaldehyde resins and melamine-formaldehyde with or without metal salt as a porogen and subcritical drying. Chemical activation is used to modify the porosity of aerogels for potential applications in carbon dioxide uptake. Chapter 8: A brief overall conclusion to this research work is presented together with recommendations for future research.